SEAWEED'S GLOBAL VALUE CHAIN AND LOCAL ECONOMIC EMPOWERMENT - Hidayat, Alfian; Safitri, Purnami (Universitas Muhammadiyah Yogyakarta, 2019)
The research analyzes the Seaweedâ€™s Global Value Chain in West Nusa Tenggara since it is treated as main export commodity of the province. The research focused on first, the governance or institutional setting of seaweed production, the governance type of seaweedâ€™s trade plot which link the farmers, collective trader, and main trader and at last the global buyer. The research uses descriptive-qualitative approach and located in Central Lombok, West Nusa Tenggara. Data sources are gathered by observation in the field and in-depth interview with respondents. The research also used literatures data to enrich and broadening the perspective. Miles and Huberman models are used as analysis technique during in the field research. The model itself consists of data reduction activity, data display and conclusion, and data drawing or data verification. The result of this research shows that the institutional setting of seaweed production has not been well managed yet, which is indicated by the overlapping of structure, function and duties of several bureaucracy institutions. Second, the local competitiveness in seaweed trade is still weak.Â Third, the upgrading capacity to process and diversified the commodity remains low because the industrialization is merely reckon on small-medium size industries. Fourth, government efforts in enhancing the upgrading capacity frequently limited at the technique aspects, meaning the institutional setting to enforce the synergy between actors is considered poor.